2020
DOI: 10.3233/jad-200443
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Nutraceuticals and Phytochemicals in the Prevention and Treatment of Alzheimer’s Disease

Abstract: One of the major challenges of medical sciences has been finding a reliable compound for the pharmacological treatment of Alzheimer’s disease (AD). As most of the drugs directed to a variety of targets have failed in finding a medical solution, natural products from Ayurvedic medicine or nutraceutical compounds emerge as a viable preventive therapeutics’ pathway. Considering that AD is a multifactorial disease, nutraceutical compounds offer the advantage of a multitarget approach, tagging different molecular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 138 publications
0
43
0
1
Order By: Relevance
“…The nutraceutical NT-020, which is a proprietary blend of blueberries, green tea, vitamin D3, and carnosine, has been shown to reduce inflammation in elderly rats and prevent age-related cognitive decline and enhance neurogenesis [ 484 , 485 , 486 , 487 , 488 ]. Treating aged rats with NT-020 increases neurogenesis and serum from these animals’ rescued aged hippocampal neural stem/precursor cells (NPCs) and bone-marrow derived mesenchymal stem cells (MSCs) from age-related reduction in cell proliferation as measured by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and 5-bromo-2′-deoxyuridine (BrdU) assays and serum from aged rats treated with NT-020 was not different from serum.…”
Section: Possible Intervention For Neuroinflammation In Admentioning
confidence: 99%
“…The nutraceutical NT-020, which is a proprietary blend of blueberries, green tea, vitamin D3, and carnosine, has been shown to reduce inflammation in elderly rats and prevent age-related cognitive decline and enhance neurogenesis [ 484 , 485 , 486 , 487 , 488 ]. Treating aged rats with NT-020 increases neurogenesis and serum from these animals’ rescued aged hippocampal neural stem/precursor cells (NPCs) and bone-marrow derived mesenchymal stem cells (MSCs) from age-related reduction in cell proliferation as measured by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and 5-bromo-2′-deoxyuridine (BrdU) assays and serum from aged rats treated with NT-020 was not different from serum.…”
Section: Possible Intervention For Neuroinflammation In Admentioning
confidence: 99%
“…122 Inhibition of brain inflammation could be accomplished with natural molecules, especially the polyphenolic flavonoids. [123][124][125][126][127] The flavone luteolin improved AD 128,129 and other disorders via different mechanisms (Table 1). 130 These include inhibiting activation of microglia, 131,132 inhibiting AchE 133 and preventing Ab42 plaque formation, 134 inhibiting fibrillary β-amyloidinduced inflammation, 135 reducing zinc-induced tau phosphorylation 136 as well as inhibiting reducing mucintype O-gycosylation of amyloid precursor protein, 137 thus resulting in increased memory in rodent models of AD.…”
Section: Anti-inflammatory Treatment Approachesmentioning
confidence: 99%
“…Inhibition of brain inflammation could be accomplished with natural molecules, especially the polyphenolic flavonoids 123–127 . The flavone luteolin improved AD 128,129 and other disorders via different mechanisms (Table 1).…”
Section: The Role Of Microgliamentioning
confidence: 99%
“…Another recent study has shown that nutraceuticals such as luteolin can enhance memory in AD patients. 74 AD and TBI-induced beta-amyloid (Aβ) level, phospho tau (p-tau), glycogen synthase-3 (GSK-3), and inflammatory cytokine/chemokine levels were reduced by peripheral administration of luteolin in mice. 75 Luteolin reduced TBI-induced elevation of IL-1β, neuronal death, brain edema, BBB disorders, and activation of the transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2)-ARE and protected the brain from secondary brain injury in mice.…”
Section: Neuroprotective Effects Of Luteolin In Neuroinflammatory Dmentioning
confidence: 99%
“…However, the exact mechanism involved in this luteolin's neuroprotective effects are not clearly understood. Another recent study has shown that nutraceuticals such as luteolin can enhance memory in AD patients 74 . AD and TBI‐induced beta‐amyloid (Aβ) level, phospho tau (p‐tau), glycogen synthase‐3 (GSK‐3), and inflammatory cytokine/chemokine levels were reduced by peripheral administration of luteolin in mice 75 .…”
Section: Neuroprotective Effects Of Luteolin In Neuroinflammatory Disordersmentioning
confidence: 99%